2022
DOI: 10.1371/journal.pone.0276432
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of ecosystem services: Comparing socio-cultural and environmental influences

Abstract: Ecosystem services such as food provisioning, climate regulation, nutrient cycling, or recreation in open landscapes underpin human wellbeing. They are highly dependent on land use, land cover and utilization pattern as well as environmental factors like climate, topography and soil. In consequence, ecosystem services supply shows a high spatial variability. However, it is less clear if the perception of the importance of ecosystem services is similarly heterogeneous in space and amongst societal actors. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Although nature managers may not be scientists, the majority in our sample hold a university degree, indicating a scientific background. Similarly, in a study on ecosystem services perceptions in Bavaria, Germany, Thiemann et al ( 2022 ) found that habitat services were perceived to be very important for over 90% of the nature managers that responded to the survey.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Although nature managers may not be scientists, the majority in our sample hold a university degree, indicating a scientific background. Similarly, in a study on ecosystem services perceptions in Bavaria, Germany, Thiemann et al ( 2022 ) found that habitat services were perceived to be very important for over 90% of the nature managers that responded to the survey.…”
Section: Discussionmentioning
confidence: 92%
“…We also collected data on socio-demographic and sectoral factors, such as farm management. Other parts of the survey focused on perceptions of ecosystem services (Thiemann et al 2022 ), landscape elements (Küchen et al 2023 ), and climate change (Landwehr et al 2023 ). The mentioned studies include all four sampled societal actor groups (comprising foresters and citizens).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation